2014
DOI: 10.1080/10942912.2013.784333
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profile ofSatureja KitaibeliiWierzb. ex Heuff. Essential Oils: Composition ofSatureja KitaibeliiEssential Oils

Abstract: The essential oils from dried aerial parts of Satureja kitaibelii Wierzb. ex Heuff., collected at three various sites in Serbia, were analyzed by gas chromatography and gas chromatography/mass spectrometry. One hundred sixty-three components were identified in all investigated samples, 132 components in the oil from the site Devojački grob, 124 components in the oil coming from Sićevačka klisura site, and 146 components in the oil from the site Visočka Ržana, accounting 97.3, 93.9, and 95.6% of the total oils,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…Sacchetti et al [17] reported that the R. officinalis of Sardinian ecotype is rich in verbenone, camphor, bornyl acetate, and borneol. The [13] Sharififar et al, [4] Azizi and Davareenejad, [5] Shahsavari et al, [9] Đorđević et al, [12] Dawidowicz and Olszowy, [14] Hashemi et al, [15] Mazidi et al, [16] and Sacchetti et al [17] IMPROVING STABILITY OF OLIVE OIL BY ESSENTIAL OILS Sardinian ecotype of R. officinalis shows better AA than those reported by Baratta et al [8] who worked on samples of other R. officinalis ecotypes with regard to their α-pinene/1,8-cineole/ camphor chemotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sacchetti et al [17] reported that the R. officinalis of Sardinian ecotype is rich in verbenone, camphor, bornyl acetate, and borneol. The [13] Sharififar et al, [4] Azizi and Davareenejad, [5] Shahsavari et al, [9] Đorđević et al, [12] Dawidowicz and Olszowy, [14] Hashemi et al, [15] Mazidi et al, [16] and Sacchetti et al [17] IMPROVING STABILITY OF OLIVE OIL BY ESSENTIAL OILS Sardinian ecotype of R. officinalis shows better AA than those reported by Baratta et al [8] who worked on samples of other R. officinalis ecotypes with regard to their α-pinene/1,8-cineole/ camphor chemotype.…”
Section: Discussionmentioning
confidence: 99%
“…EO samples were dried over anhydrous sodium sulphate and were stored in sealed vials at -18°C for further use. [12] Gas Chromatography (GC) Analysis of EOs…”
Section: Extraction Of Eomentioning
confidence: 99%
See 1 more Smart Citation
“…S. kitaibelii EO constituents from this study and from literature reports [18,[36][37][38][39][40] are shown in Table 3. The classification between them according to the content of chemical compounds was performed using HCA analysis (Figure 1a).…”
Section: Satureja Kitaibeliimentioning
confidence: 99%
“…The main phytochemical studies on the variability of EO compositions of S. kitaibelii were conducted at populations in Serbia and the former Yugoslavia [ 7 , 15 , 18 , 19 ] ( Table 1 ). The EO composition of S. kitaibelii varied considerably in the samples from Serbia [ 20 ]. The cited authors found differences between the populations of S. kitaibelii in terms of the EO composition and the presence of chemotypes, namely geraniol, p -cymene, and limonene, with a high abundance of linalool and borneol [ 7 , 20 ].…”
Section: Introductionmentioning
confidence: 99%